2011
DOI: 10.3892/etm.2011.199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise and high-fat diet on plasma adiponectin and nesfatin levels in mice

Abstract: Abstract. lifestyle-related diseases are associated with overeating and lack of exercise. the purpose of this study was to investigate the effect of exercise and high-fat diet on plasma adiponectin and nesfatin levels. mice were housed for 4 weeks in 4 groups, which included the non-exercise and normal diet (Sn), exercise and normal diet (En), non-exercise and high-fat diet (SF) and the exercise and high-fat diet (EF) group. the mice in the exercise groups were housed in cages with a running wheel and were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 24 publications
6
23
2
1
Order By: Relevance
“…This finding came along with the responses to appetite questionnaires which indicated less desire to eat, less perceived hunger, less craving for carbohydrates and lower scores on "how much food can you eat" questions. These findings are in agreement with the results of Chaolu et al (2011) who showed that four weeks of endurance training increased plasma nesfatin-1 level. Shimizu et al (2009) found that the intraperitoneal administration of nesfatin-1 inhibits food intake and thereby reduces body weight (Shimizu et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…This finding came along with the responses to appetite questionnaires which indicated less desire to eat, less perceived hunger, less craving for carbohydrates and lower scores on "how much food can you eat" questions. These findings are in agreement with the results of Chaolu et al (2011) who showed that four weeks of endurance training increased plasma nesfatin-1 level. Shimizu et al (2009) found that the intraperitoneal administration of nesfatin-1 inhibits food intake and thereby reduces body weight (Shimizu et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Our data are consistent with those studies who's investigated the effects of different mode acute/ chronic exercise training on plasma nesfatin-1 in human and animal subjects [69][70][71][72]. In our study, we observed a lower ghrelin mRNA expression in both saline and Bane-trained liver, not in visceral fat tissue.…”
Section: Figure 8 Plasma Estradiol Level In Different Groupssupporting
confidence: 82%
“…However, to our knowledge, the capacity of different exercise training programs to alter nesfatin has yet to be fully investigated. Only few studies have investigated the effects of short-term ( < 20 min) acute exercises (including human study) [17] or exercise training and diet on nesfatin-1, which has been carried out in mice [18,19] . Physical exercise is an essential part of any weight management program and an effective method to reduce the risk of insulin resistance and chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%